Gestational intermittent hypoxia reduces mandibular growth with decreased Sox9 expression and increased Hif1a expression in male offspring rats - Suzuki, Takumi; Hosomichi, Jun; Maeda, Hideyuki; Ishida, Yuji; Usumi-Fujita, Risa; Moro, Manaka; Jariyatheerawong, Korkuan; Ono, Takashi (Frontiers in Physiology, 2024)
Introduction: Maternal obstructive sleep apnea (OSA) during pregnancy is the risk factor for impaired fetal growth with low birth weight in the offspring. However, it is unclear whether gestational intermittent hypoxia (IH, a hallmark of maternal OSA) has long-term detrimental consequences on the skeletal development of offspring. This study aimed to investigate postnatal maxillofacial bone growth and cartilage metabolism in male and female offspring that were exposed to gestational IH.Mother rats underwent IH at 20 cycles/h (nadir, 4% O2; peak, 1% O2; 0% CO2) for 8 h per day during gestational days (GD) 7-20, and their male and female offspring were analyzed postnatally at 5 and 10 weeks of age. All male and female offspring were born and raised under normoxic conditions. Results: There was no significant difference in whole-body weight and tibial length between the IH male/female offspring and their control counterparts. In contrast, the mandibular condylar length was significantly shorter in the IH male offspring than in the control male offspring at 5 and 10 weeks of age, while there was no significant difference in the female offspring. Real-time polymerase chain reaction (PCR) showed that gestational IH significantly downregulated the mRNA level of SOX9 (a chondrogenesis marker) and upregulated the mRNA level of HIF-1α (a hypoxia-inducible factor marker) in the mandibular condylar cartilage of male offspring, but not in female offspring.Gestational IH induced underdeveloped mandibular ramus/condyles and reduced mRNA expression of SOX9, while enhancing mRNA expression of HIF-1α in a sex-dependent manner.